The Psychological Barrier Towards Devotion of Relationship in The Notebook by Nicholas Sparks - Eri Yuliyanti Kadjan; Adi Prautomo (Faculty of Letters Universitas Balikpapan, 2023)
This research studies of Psychological Barrier Toward Devotion Of Relationship In The Novel Notebook by Nicholas Sparks. There are two objectives of this research; 1). What psychological barrier are faced by the main character in the novel 2). How does the main character devote to his relationship. The theory used in this research is the Individual Psychology theory according to Alfred Adler with structural two elements as such inferiority feeling and striving for superiority. The methodology employed is qualitative research with the primary data in which the researcher tried to present the issues descriptively. As for the data, they were collected from the novel. While the secondary data and other related sources. The data were collected through library research. The result of the research, the researcher found the factor of psycholgy barrier and Devotion which contains in two elements. Meanwhile, the researcher found that there are three factor from psychological barrier such as incapability of physical health, social status, and lack of support. The factor of devotion are four such as consistenly, trustworthy, patiently, and sacrifice to portray from main character.